Peran Perempuan dalam Pemenuhan Kebutuhan Ekonomi Keluarga di Desa Sumberingin Kulon Kecamatan Ngunut Kabupaten Tulungagung - Yuniasari, Fenni (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2020)
Abstract Woman’s role the more days ate more expand along with the development of Science and Technology. Not only in the domestic sector, woman’s role alredy very wide in the economy world because demand for the economics needs of the family that day by day more increased. This research aims to determine the shape of the woman’s role in fulfill the economic needs of the family, the problems that woman face in her role to help fulfill the economic needs of the family and the impact of woman’s role in her effort to help fulfill the economic needs of the family. This research method uses a qualitative approach with field research type, while tis research is descriptive. Data collection techniques performed with interview, observation, and documentation. Sample selection using purposive sample by taking research subjects that fulfill the criteria. The result of this research indicate that the woman’s role is very large in effort to help fulfill the economic needs of the family. Woman work in their own homes as brick makers and also work as laborers in the roof-tile manufacturing industry. Many obstacles that woman face such as decreased production during the rainy season, obstacles in the procurement of good quality materials and difficult to devide the time. The impacts of working woman are very diverse, there are positive and negative impacts. The positive impacts is help to fulfill the economic needs of the family, having savings and improving family status. The negative impact in time taking up time to do housework. Keywords:woman’s role, economic needs, family